TQM-Based Curriculum Sanctioning and Transdisciplinary Collaboration as a Strategy for Attaining International Accreditation: A Case Study of the Educational Management Department at UNESA - Amalia, Kaniati; Zawawi, Ahmad Abdullah; Museyibzada, Rabiyya (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2025)
Objective: This study investigates how the integration of Total Quality Management (TQM) and transdisciplinary collaboration supports the curriculum restructuring process at the Department of Educational Management, Universitas Negeri Surabaya (UNESA), in achieving international accreditation standards set by ACQUIN. The abstract clearly and succinctly outlines the process of curriculum reform, emphasizing the systematic stages and quality framework applied. Method: A qualitative descriptive method was applied to explore the institutional strategies and processes involved in curriculum reform. Data were collected through observations, interviews, and documentation involving internal and external stakeholders, including lecturers, students, international academics, and partner institutions. The data were analyzed using Miles and Huberman’s interactive model, focusing on the stages of planning, implementation, and evaluation. Results: The curriculum restructuring process followed three systematic stages: internal review, external review, and sanctioning meetings. Each stage was guided by the PDCA (Plan–Do–Check–Act) cycle, ensuring that quality assurance, reflection, and continuous improvement were embedded throughout the process. Multi-stakeholder participation was central to every stage, promoting alignment with international standards and responsiveness to both institutional and global needs. Transdisciplinary collaboration particularly with academics from Malaysia and Thailand, as well as local NGOs enhanced curriculum content, learning outcomes, and pedagogical design, ensuring both contextual relevance and international compatibility. Novelty: This study proposes a quality-based curriculum management model that integrates TQM principles with transdisciplinary collaboration. Unlike conventional curriculum reforms, this model positions quality assurance mechanisms and global collaboration as the core drivers of sustainable change. The findings provide both practical and theoretical insights for higher education institutions seeking international recognition, demonstrating that structured, quality-driven curriculum restructuring can strengthen institutional competitiveness and educational relevance in the global landscape.